A Discourse Analysis of Mission Statements of American and Vietnamese Universities - Vũ Thị Hoài Vân (2011)
Based on the theories of Discourse Analysis, this study focuses on describing and analyzing some typical discourse features in terms of the layout, lexical features, syntactic structures and cohesive devices between American University Mission Statements.